Teacher-Student Interaction: Direct Instruction versus Suggestive Instruction - Parashar, Kapila (THE PRIMARY TEACHER, 2019)
The core element in all academic discourse is pedagogical practice. To engage learners actively, to interest them in the content, to guide them to correct their mistakes, and to make them independent learners, teachers need to regularly interact with students. Teacher-student interaction is an important aspect of learning as it creates opportunities for the learners to construct their knowledge including language with the help of a more knowledgeable and expert person, i.e., their teacher. A teacher-led interaction may be direct or indirect in class; it may facilitate learners in comprehension, or at times may confuse the learners in comprehending the message of the teacher. The reasons for students to get confused include differences in cultural context and the requirements of the learning situation in the classroom. The learning process is affected due to differences in the interaction styles of teachers and students. Identification of the communication style, conscious efforts by the learners to understand the message, and careful planning of the classroom processes that include direct as well as indirect communication style by the teacher can help the learners to own their learning and to help the teachers to be more effective.